Debridement with high speed burr reduce more colonies of Staphylococcus aureus in chronic osteomyelitis of rabbit’s tibia compare to debridement with curettage - Rante, Su Djie To; Handoyo, Henry Ricardo (International Journal of Research in Medical Sciences, 2016)
Background: Chronic osteomyelitis has been a difficult problem for the patient and for the treating physician. Chronic osteomyelitis is defined by most authors as osteomyelitis with symptoms that have been present for more than 1 month. Chronic osteomyelitis also defined by an infected dead bone within compromise soft tissue. An aggressive debridement and specific antibiotic treatment is first choice for chronic osteomyelitis. The purpose of this study was to assess the reduction in the number of colonies of Staphylococcus aureus after debridement with a high speed burr compared to debridement with curettage. Methods: This study is an experimental study was designed using a randomized post-test only group design. A total of 42 rabbits inoculated his right tibia with 0.1 ml Staphylococcus aureus 107 CFU / ml, and then inserted with K-wire intramedullary. Two weeks after inoculation, chronic osteomyelitis occurs, grade 3 and 4 radiologically. Then 10 rabbits were sacrificed without debridement, colonies of germs counted as control, 16 rabbits was performed debridement with curettage and 16 rabbits was performed debridement with high speed burr. Three weeks after debridement, 32 rabbits was sacrificed and counted for final germs colonies. Results: The results obtained from debridement with high speed burr and debridement with curettage, number of colonies of Staphylococcus aureus is less than the number of control’s colonies, with a value of p = 0.006 (p <0.05), debridement with a high speed burr also decrease the number of colonies of Staphylococcus aureus compared to debridement with curettage, with p = 0.023 (p<0.05), odds ratio of 9.000 (CI=95%). This is shows that this difference is statistically significant. Conclusions: The data showed that debridement with a high speed burr more likely to decrease the number of colonies of germs that can be recommended as a method of debridement for chronic osteomyelitis.